Comparison of diagnostic value of visual inspection with Lugol’s iodine to conventional Paps smear in detection of colposcopic biopsy proved CIN: a tertiary care experience - Bajaj, Manisha; Ahmad, Shamshad; Trivedi, Shubha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: An organized cytological screening (Pap smear) is the mainstay for cervical cancer prevention and control programme. Financial and logistic burden of operating such a program is considerable. This has prompted the evaluation of alternative feasible techniques. It appeared from the earlier studies that visual inspection with lugol’s iodine (VILI) could be a potential alternative to cervical cytology. VILI is a low cost, easy to apply and highly sensitive technique. It gives result immediately thus allows doctors to “see and treat” at first visit. Objective of present study was to evaluate the performance of visual inspection with lugol’s iodine and its comparison with cytology in cervical cancer screening. Methods: 400 non-pregnant reproductive age women were subjected to Paps and VILI in this prospective study done in a tertiary-care centre in Delhi. Reference standard used for all was colposcopy and colposcopic-directed biopsy (when required). Results: Of 400 Pap smears done 11.75% were normal, 77.5% inflammatory, 5.5% had ASCUS, 0.25% ASC-H, 0.5% AGUS, 2% LSIL, 1.5% HSIL and invasive cancer in 0.5%. With LSIL and above smears as significant, the sensitivity and specificity of Paps were 50% and 97.66% respectively. VILI was positive in 12.8% of cases. Sensitivity and specificity of VILI was 85.5% and 89.9% respectively. Overall accuracy of VILI in detecting pre-invasive lesion was 89.7% while with pap smear it was 96%. Conclusions: Accuracy of VILI and Pap smear in detecting pre-invasive cervical lesion was comparable. At tertiary-care centers VILI can be used effectively to screen the patients with significant lesions. Patients can be directly subjected to further treatment at the earliest thus reducing loss to follow-up.